Dynamic analysis and position control of a single flexible-link flexible-joint robot manipulator using time delay - Dong, Yuan (University of Ottawa (Canada), 2006)
In this thesis, a position control system for a single flexible-link flexible-joint (FLFJ) manipulator has been developed. It is presented in three parts: dynamic modeling and analysis, control system design, and experimental analysis of the designed control system. The assumed modes method and the Lagrange approach were combined to derive a dynamic model of the single FLFJ manipulator and then this model was linearized about zero deflection for both the flexible joint and the flexible link. The resulting linear dynamic model was used for the dynamic analysis and control system design. Equations of motion and their analytical solutions were derived for the single FLFJ manipulator at any rotation angle. The effects of the relative stiffness of the joint with respect to the link on the dynamic characteristics and open-loop responses of the single FLFJ manipulator were investigated based on the linear model. It was found that the higher order frequencies of the manipulator increased monotonically with the increments of the joint stiffness, while the lower order ones kept almost unchanged. This demonstrates that the higher order frequencies were more sensitive to the interaction between the flexible link and the flexible joint. A time-Delayed Feedback Signal (DFS) controller was applied to the single FLFJ manipulator and the effect of the time delay on the stability of the system was examined. (Abstract shortened by UMI.)
Keywords: Engineering, Mechanical.